Transcriptome profiles of tomato plants after neutron irradiation and infection with TYLCV. Issue 2 (26th January 2019) - Zhou, Yujie; Cho, Won Kyong; Byun, Hee‐Seong; Kil, Eui‐Joon; Bak, Sang‐In; Moon, Dal‐Ho; Chavan, Vivek; Park, Tae‐Sun; Lee, Sukchan; Hong, Seung‐Woo
Abstract : Ionizing radiation is ubiquitous in the environment and can cause mutagenesis in living organisms. In this study, we examined the effects of neutron irradiation on tomato plants. Neutron irradiation decreased tomato germination rates, but most irradiated tomato plants did not show any significant phenotype. However, tomato mutants infected by Tomato yellow leaf curl virus (TYLCV) displayed resistance against TYLCV compared to the wild type (WT), which showed disease symptoms. RNA‐Seq data demonstrated that the expression profiles of eight tomato mutants were significantly different from that of the WT. The transcriptomes obtained from presoaked seeds were highly altered compared to those of dry seeds. Increased irradiation time resulted in severe changes in the tomato transcriptome; however, different neutron irradiation intensities affected the expressions of different sets of genes. A high number of single‐nucleotide polymorphisms in tomato transcriptomes suggest that neutron irradiation strongly impacts plant transcriptomes. The transition/transversion values among mutants were almost constant and were lower than that of the non‐irradiated sample (WT), suggesting that neutron irradiation caused an effect. Taken together, this is the first report showing the effects of neutron irradiation on tomato plants by transcriptome analyses.